International Inflation Spillovers Through Input Linkages - Raphael A. Auer; Andrei A. Levchenko; Philip Sauré (Center for Economic Studies and ifo Institute (CESifo), 2017)
We document that observed international input-output linkages contribute substantially to synchronizing producer price inflation (PPI) across countries. Using a multi-country, industry-level dataset that combines information on PPI and exchange rates with international and domestic input-output linkages, we recover the underlying cost shocks that are propagated internationally via the global input-output network, thus generating the observed dynamics of PPI. We then compare the extent to which common global factors account for the variation in actual PPI and in the underlying cost shocks. Our main finding is that across a range of econometric tests, input-output linkages account for half of the global component of PPI inflation. We report three additional findings: (i) the results are similar when allowing for imperfect cost pass-through and demand complementarities; (ii) PPI synchronization across countries is driven primarily by common sectoral shocks and input-output linkages amplify co-movement primarily by propagating sectoral shocks; and (iii) the observed pattern of international input use preserves fat-tailed idiosyncratic shocks and thus leads to a fat-tailed distribution of inflation rates, i.e., periods of disination and high inflation.
Keywords: E31; E52; E58; F02; F14; F33; F41; F42; F62; 330; international inflation synchronization; globalization; inflation; input linkages; monetary policy; global value chain; production structure; input-output linkages; supply chain